Volumetric properties of paranasal sinuses in thin-section craniofacial computedtomography images using interactive segmentation method - VERİMLİ, URAL; ÇİMŞİT, NURİ ÇAGATAY; BUĞDAYCI, ONUR (My University, 2021)
Aim: The aim of this study is to examine the volumetric properties of the paranasal sinuses by creating threedimensional reconstructions of high-resolution images obtained by computed tomography by interactive segmentation method. Material and Methods: Thin-section multidetector computed tomography images of 40 female and 40 male individuals between the ages of 20-40 without cranium pathology will be evaluated retrospectively. The volumetric characteristics of the paranasal sinuses will be evaluated in terms of the age and gender of the sample group. The observed variations and mucosal thickness changes in the sinus walls will be determined. Computed Tomography images were transferred to the Imfusion Suite Demo software and volume measurement was performed separately for the right and left by segmentation method. Results: In our study, a statistically significant difference was observed between male individuals for sphenoidal sinus (p=0.0354), and a gender-related difference was observed for frontal sinus (p=0.0033) and maxillaris sinus (p=0.0104) in the same age group. Conclusion: Eventually we aim to obtain comprehensive morphometric information for paranasal sinuses and provide crucial information for clinical applications. Measurement, examination and analysis of paranasal sinus volumes are expected to reduce time required and benefit the anatomical outcomes for certain surgical interventions.
Keywords: Three-dimensional reconstruction; frontal sinus; sphenoidal sinus; maxillary sinus; volume